Future Eco‐Perfect: Temporal Fixes of Liberal Environmentalism. Issue 5 (25th May 2022) - Collard, Rosemary‐Claire; Dempsey, Jessica
Abstract: In the last half century runaway wildlife declines have been simultaneous with the liberal environmental state's ascent. Despite proliferating legislation to arrest these declines, states have fuelled economic growth at species' expense. Through what tactics of power does the liberal environmental state manage this contradiction between promising species protection while authorising their obliteration? Manipulations of tense, futurity, temporal pace and scope are central. Responding to the plight of endangered caribou in Canada, the state tinkers and repeatedly resets time ("starting … now!") while hailing the future eco‐perfect, a time just‐around‐the‐corner when caribou and the economy will flourish.